Cannabis use in patients with early psychosis is associated with alterations in putamen and thalamic shape. Issue 15 (20th July 2020) - Sami, Musa; Cole, James H.; Kempton, Matthew J.; Annibale, Luciano; Das, Debasis; Kelbrick, Marlene; Eranti, Savitha; Collier, Tracy; Onyejiaka, Chidimma; O'Neill, Aisling; Lythgoe, David J.; McGuire, Philip; et al.
Abstract: Around half of patients with early psychosis have a history of cannabis use. We aimed to determine if there are neurobiological differences in these the subgroups of persons with psychosis with and without a history of cannabis use. We expected to see regional deflations in hippocampus as a neurotoxic effect and regional inflations in striatal regions implicated in addictive processes. Volumetric, T1w MRIs were acquired from people with a diagnosis psychosis with (PwP + C = 28) or without (PwP − C = 26) a history of cannabis use; and Controls with (C + C = 16) or without (C − C = 22) cannabis use. We undertook vertex‐based shape analysis of the brainstem, amygdala, hippocampus, globus pallidus, nucleus accumbens, caudate, putamen, thalamus using FSL FIRST. Clusters were defined through Threshold Free Cluster Enhancement and Family Wise Error was set at p < .05. We adjusted analyses for age, sex, tobacco and alcohol use. The putamen (bilaterally) and the right thalamus showed regional enlargement in PwP + C versus PwP − C. There were no areas of regional deflation. There were no significant differences between C + C and C − C. Cannabis use in participants with psychosis is associated with morphological alterations in subcortical structures. Putamen and thalamic enlargement may be related to compulsivity in patients with a history of cannabis use. Abstract : Cannabis is often associated with the early course of psychotic disorders. The EfCIP study looked at four groups: People with psychosis with cannabis use, people with psychosis without cannabis use, controls with cannabis use and controls without cannabis use. We observe change in subcortical morphology in persons with psychosis with cannabis use versus persons with psychosis without cannabis use in the putamen and thalamus which may be due to compulsive use in this group.